LIQUIDITY RISK AND FINANCIAL PERFORMANCE OF LISTED DEPOSIT MONEY BANKS IN NIGERIA - Bashir Abdulrauf Mohammed; Aliyu Ahmed Abdullah; Ibrahim Yusuf; Suleiman Salami; Prof. Salisu Mamman (Gusau Journal of Accounting and Finance, 2024)
This study examines the effect of liquidity risk on financial performance of listed deposit money banks in Nigeria. The correlation research design was adopted based on positivist approach. Secondary data were extracted from twelve listed deposit money banks in the Nigerian Exchange Group (NEGX) from (2013 -2022) and analyzed using multiple regression technique. The study was under pin by risk management theory. The result of the Generalized Least Square Regression model showed that current risk has positive association with financial performance at 5% level of significant while cash reserve risk has a negative significant effect on financial performance of listed deposit money banks in Nigeria significant at 1%. In line with the findings, the study recommends among others; the management of the banks should recheck the need for recapitalization as doing this will enhance the capability of the banks in financing large transactions and resolving mismatching challenges as owners fund will be available for long term financing. The study also recommended that, the management of the banks should ensure compliance by keeping required amount in liquid as directed by central bank of Nigeria, as doing this will enable the banks to meet possible unexpected cash withdrawal, immature term deposit liquidation and other payable on demand which will enhance their performance. The banks’ management should always ensure compliance on regulatory directives particularly on cash reserve as doing this will reduce the possible loss and improve on their performance.